Hydrophobic and Hydrophilic Extractives in Norway Spruce and Kurile Larch and Their Role in Brown-Rot Degradation - Füchtner, Sophie; Brock-Nannestad, Theis; Smeds, Annika; Fredriksson, Maria; Pilgård, Annica; Thygesen, Lisbeth Garbrecht (Frontiers in Plant Science, 2020)
Extractives found in the heartwood of a moderately durable conifer (Larix gmelinii var. japonica) were compared with those found in a non-durable one (Picea abies). We identified and quantified heartwood extractives by extraction with solvents of different polarities and gas chromatography with mass spectral detection (GC-MS). Among the extracted compounds, there was a much higher amount of hydrophilic phenolics in larch (flavonoids) than in spruce (lignans). Both species had similar resin acid and fatty acid contents. The hydrophobic resin components are considered fungitoxic and the more hydrophilic components are known for their antioxidant activity. To ascertain the importance of the different classes of extractives, samples were partially extracted prior to subjection to the brown-rot fungus Rhodonia placenta for 2-8 weeks. Results indicated that the most important (but rather inefficient) defense in spruce came from the fungitoxic resin, while large amounts of flavonoids played a key role in larch defense. Possible moisture exclusion effects of larch extractives were quantified via the equilibrium moisture content of partially extracted samples, but were found to be too small to play any significant role in the defense against incipient brow-rot attack.